Flexible electronics for heavy metal ion detection in water: a comprehensive review. - Leburu, Ely; Qiao, Yuting; Wang, Yanshen; Yang, Jiakuan; Liang, Sha; Yu, Wenbo; Yuan, Shushan; Duan, Huabo; Huang, Liang; Hu, Jingping; Hou, Huijie (Biomedical Microdevices, 2024)
Flexible electronics offer a versatile, rapid, cost-effective and portable solution to monitor water contamination, which poses serious threat to the environment and human health. This review paper presents a comprehensive exploration of the versatile platforms of flexible electronics in the context of heavy metal ion detection in water systems. The review overviews of the fundamental principles of heavy metal ion detection, surveys the state-of-the-art materials and fabrication techniques for flexible sensors, analyses key performance metrics and limitations, and discusses future opportunities and challenges. By highlighting recent advances in nanomaterials, polymers, wireless integration, and sustainability, this review aims to serve as an essential resource for researchers, engineers, and policy makers seeking to address the critical challenge of heavy metal contamination in water resources. The versatile promise of flexible electronics is thoroughly elucidated to inspire continued innovation in this emerging technology arena.